Pengembangan Sumber Daya Manusia Melalui Manajemen Sumber Daya Manusia Elektronik: Studi Literatur - Edi Irawan (Lembaga Pengembangan Kinerja Dosen, 2023)
This article aims to review and seek to inform about the concept of human resource development through electronic human resource management. The research method used is qualitative and literature studies or library research. Based on the results of the discussion above, it can be concluded that the recruitment process carried out electronically/online ( e-recruitment ) can help organizations attract more diverse applicants. The choice to move to the e-recruitment model was driven by several organizational objectives, including the need for the following: (a) Increase recruitment efficiency and reduce costs, (b) Increase the quality and quantity of applicants, e-recruiting which enables organizations to easily reach applicants in all corners of the country and even around the world, (c ) Build, communicate and expand brand identity, as means of business promotion that can attract applicants to join the organization, (d) Increase objectivity and standardize recruiting practices, (e) Increase applicant convenience, potential applicants will take advantage of web-based support for the hiring cycle to learn about and find out about the company’s activities, culture and opportunities online.